GENES EXPRESSED IN SILK GLANDS OF Bombyx mori SHOW DIFFERENTIAL ASSOCIATION WITH NUCLEAR MATRIX DURING 5TH INSTAR DEVELOPMENT (Applied Biological Research, 2023)
Silk glands are highly regulated during 5th instar larval development of  Bombyx mori. Several genes show up and down regulation in silk glands  during 5th instar stage. Nuclear matrix tethers chromatin and marks them  into active and inactive domains, thereby playing an important role in gene  regulation. The association of differentially regulated genes of silk glands to  nuclear matrix has not been studied earlier. The present study explored the  binding of genes to nuclear matrix and their differential  expression. The association to nuclear matrix of the selected genes was  studied using in-silico methods. The MAR Finder analysis showed high  MAR binding potential for all the genes selected. The number of MAR  binding sites varied from day 1 to day 7. Differences were observed in MAR sites during development often coincided with differential expression of  genes. This study gives a new perspective in the understanding of  differential gene regulation in silk gland development.
Keywords: Bombyx mori; nuclear matrix; MAR; silk gland; gene regulation